The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/ams2.341
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics distinguishing abusive head trauma from accidental head trauma in infants with traumatic intracranial hemorrhage in Japan

Abstract: AimTo identify markers for detecting abusive head trauma (AHT) and its characteristics in the Japanese population.MethodsWe retrospectively reviewed the clinical records of 166 infants with traumatic intracranial hemorrhage between 2002 and 2013 in three tertiary institutions in Japan. The infants were classified into AHT (57), suspected AHT (24), and accidental (85) group based on the defined criteria. We compared clinical presentations and computed tomography findings among these three groups and also compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…A previous study reported that about 10% of burn cases were suspected abuse cases 16 . Concerning to abuse and/or neglect, one observational study from Japan reported that about half of the traumatic intracranial hemorrhage was caused by abuse 17 . Though abuse data was not registered in JTDB and the association between pediatric burns and abuse could not investigated, the high prevalence of pediatric burns in children <1 year clinicians suspected abuse and/or neglect.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that about 10% of burn cases were suspected abuse cases 16 . Concerning to abuse and/or neglect, one observational study from Japan reported that about half of the traumatic intracranial hemorrhage was caused by abuse 17 . Though abuse data was not registered in JTDB and the association between pediatric burns and abuse could not investigated, the high prevalence of pediatric burns in children <1 year clinicians suspected abuse and/or neglect.…”
Section: Discussionmentioning
confidence: 99%
“…And yet, mathematical partition based on objective, reliably determined clinical variables replicated the results of decades of literature on the characteristics of children with AHT. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] By replicating the segregation of clinical findings in the case-control literature, the cluster analyses demonstrate that the division of cases from controls reflected natural latent divisions in the larger population of young children with neurotrauma. The fact that these differences extended beyond neurologic and eye findings to include skeletal fractures, skin injuries, and visceral injuries supports the inference that inflicted trauma was closely related to the latent variable responsible for partition.…”
Section: Discussionmentioning
confidence: 97%
“…The evidence base for diagnosing AHT in children with neurotrauma relies on a series of case-control studies and meta-analyses of those studies. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Cohorts of AHT cases have been separated from controls by various methods: physician diagnosis, 15,16,22 consensus opinion of a multidisciplinary team, 14,17,18,22,23,26,28,29 predefined criteria designed to avoid indicators under study, 14,[19][20][21]29 and confessed abuse versus a public non-AHT event. 22 Results of the various methods have been consistent, lending strength to the findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Characteristics associated with the accident (odds ratio) (Fig. 1) 31 Comparison of age distribution of abusive head trauma (AHT) cases between our study and a study carried out in the USA 45) . Two peaks in the number of patients were observed in the AHT group, one at approximately 1-2 months and the other at 6-8 months.…”
Section: Characteristics Associated With Aht (Odds Ratio)mentioning
confidence: 91%